2019
DOI: 10.1101/842963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A highly multiplexed melt-curve assay for detecting the most prevalent carbapenemase, ESBL and AmpC genes

Abstract: AbstractResistance to third generation cephalosporins and carbapenems in Gram-negative bacteria is chiefly mediated by beta-lactamases including ESBL, AmpC and carbapenemase enzymes. Routine phenotypic detection methods do not provide timely results, and there is a lack of comprehensive molecular panels covering all important markers.An ESBL/carbapenemase HRM assay (SHV, TEM, CTX-M ESBLs, and NDM, IMP, KPC, VIM and OXA-48-like carbapenemases) and an AmpC HRM as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…For the identification of MBL-producing strains, the susceptibility and specificity of the HRMA method were 99.2% and 99.7%, respectively, and were 100% reported for the detection of carbapenemase-producing. Studies in UK, 19 Denmark, 34 and USA 35 have shown that the sensitivity and specificity of HRMA to detect class A and class B β-lactamase are more than all phenotypic methods. However, in these studies, some phenotypic methods were used to detect strains producing ESBL and bla KPC with false positives and false negatives.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For the identification of MBL-producing strains, the susceptibility and specificity of the HRMA method were 99.2% and 99.7%, respectively, and were 100% reported for the detection of carbapenemase-producing. Studies in UK, 19 Denmark, 34 and USA 35 have shown that the sensitivity and specificity of HRMA to detect class A and class B β-lactamase are more than all phenotypic methods. However, in these studies, some phenotypic methods were used to detect strains producing ESBL and bla KPC with false positives and false negatives.…”
Section: Figurementioning
confidence: 99%
“…While phenotypebased detection methods have many advantages, molecular real-time amplification techniques have gained significant acceptance because they may provide more rapid detection, increased sensitivity, and specificity, and lack the risk of carry-over contamination associated with earlier methods. 17,19 However, normalized and difference graphs were generated to assess the ability of the HRMA method to differentiate between bacterial strains. 18 This study aimed to investigate different methods in diagnosing different strains of P. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the overall diagnostic accuracy of mPCR for HAP/VAP advanced platforms have been designed incorporating electrospray ionization mass spectrometry 48 and an ESBL/carbapenemase high-resolution melt analysis assay (SHV, TEM, CTX-M ESBL families NDM, IMP, KPC, VIM and OXA-48-like carbapenemases). 49 Gastli et al evaluated the bacterial performance of the BioFire FilmArray Pneumonia Panel in a prospective observational study involving 515 respiratory specimens. 50 This mPCR platform detected at least one pathogen in 384 specimens, and demonstrated positive percentage agreement and negative percentage agreement values of 94.4% (95% CI 91.7-96.5%) and 96.0% (95% CI 95.5-96.4%), respectively, compared with culture.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…The mutation of blaCTX-M genes in order to better hydrolyse mecillinam has been reported during urinary tract infection treatment 57 , but not for TZP or other β-lactam/inhibitor combinations. The circulation of blaCTX-M variants that do not confer the ESBL phenotype, but provide resistance to TZP, has implications for molecular testing for ESBL organisms 58 , which would misclassify these isolates as 3GC resistant, and as a consequence might lead to unnecessary use of carbapenems.…”
mentioning
confidence: 99%
“…Whilst molecular diagnostics can be used to rapidly detect AMR genes 58,64 Our study has some limitations, including that we only sequenced TZP resistant/3GC susceptible isolates at our site, and utilised a large and UK wide collection of isolates for comparison. These comparison isolates were collected between 2001 and 2012, and so are not contemporary with the study isolates collected between 2014 and 2017 but serve as the best available large-scale comparator of the same demographics.…”
mentioning
confidence: 99%